The monument to the children of Villatina: commemorating innocent child victims in the context of lethally stigmatized youth in Colombia. (August 2019) - Reyes, Ana María
This article examines the monument for the children of Villatina (2004, Medellín, Colombia) that resulted from the Masacre Villatina v. Colombia Friendly Agreement put forward by the Grupo Interdisciplinario de Derechos Humanos (GIDH) to the Inter-American Commission on Human Rights (IACHR). In 1992, the Colombian police murdered eight youths ranging in age from 8 to 22 years in the Villatina neighborhood of Medellín. After long and difficult negotiations, the GIDH and IACHR brokered a Friendly Agreement (2002) between the victims' families and the government of Colombia. As a part of the reparations program, the Colombian State committed to installing a commemorative monument in a public park in downtown Medellín. While the monument was designed to recognize the dignity and honor of the youthful victims, the author argues that its emphasis on innocence tacitly endorsed the extermination of non-innocent children and young men caught in the vortex of war. Following Judith Butler's arguments regarding 'grievable' lives in Frames of War: When Is Life Grievable? (2004) and the condition of the human, the author contends that both the process of the Friendly Agreement negotiations and the resulting monument rehearse a hierarchy of humanity that casts some lives, but not all, as grievable.